Language ideologies of the transcription system Zhuyin fuhao: a symbol of Taiwanese identity. Issue 2 (3rd July 2019) - Huang, Karen
ABSTRACT: This study argues that the transcription system Zhuyin fuhao, which has been widely used in Taiwan for the last seventy years, has been reinvented as a symbol of Taiwanese identity by the Taiwanese people. With the attempt to localise and globalise in the past 30 years, different scripts have been introduced to codify or transcribe the various languages used in Taiwan. The proposed scripts were often associated with political ideologies and caused controversies. This study focuses on a public debate in 2018 on whether or not Zhuyin fuhao should be abolished. By analysing different discourses, this study shows that it is likely that in the digital age, the transcription system is no longer just a tool for learning characters, rather it has gained orthography status which distances Taiwanese from other Chinese-speaking communities. The transcription system, although originating in China, is a linguistic capital that is shared by all young Taiwanese regardless of their ethnicity and therefore has become an exclusive symbol to represent the emergent Taiwanese national identity.